2021
DOI: 10.7150/ijbs.59032
|View full text |Cite
|
Sign up to set email alerts
|

PRG-1 relieves pain and depressive-like behaviors in rats of bone cancer pain by regulation of dendritic spine in hippocampus

Abstract: Rationale: Pain and depression, which tend to occur simultaneously and share some common neural circuits and neurotransmitters, are highly prevalent complication in patients with advanced cancer. Exploring the underlying mechanisms is the cornerstone to prevent the comorbidity of chronic pain and depression in cancer patients. Plasticity-related gene 1 (PRG-1) protein regulates synaptic plasticity and brain functional reorganization during neuronal development or after cerebral lesion. Purinergic P2X7 receptor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 81 publications
1
17
0
Order By: Relevance
“…There was no signi cant difference in TWL between sham and control rats. The development trend of pain sensitivity was similar to previous studies, that is, MWT or TWL decreased signi cantly on days 5 to 21 after SHZ-88 breast cancer cells were implanted into the tibial medulla cavity of rats [2,21].…”
Section: Changes Of Pain Threshold In Bone Carcinoma Ratssupporting
confidence: 85%
See 1 more Smart Citation
“…There was no signi cant difference in TWL between sham and control rats. The development trend of pain sensitivity was similar to previous studies, that is, MWT or TWL decreased signi cantly on days 5 to 21 after SHZ-88 breast cancer cells were implanted into the tibial medulla cavity of rats [2,21].…”
Section: Changes Of Pain Threshold In Bone Carcinoma Ratssupporting
confidence: 85%
“…The rat tibial carcinoma model was established with reference to the method described by Liu et al [21]. Female SD rats were xed under anesthesia with pentobarbital sodium (40 mg/kg, i.p.…”
Section: Establishment Of Tibial Carcinoma Modelmentioning
confidence: 99%
“…A wealth of evidence has suggested that BCP is a complex clinical syndrome, that shares a number of features with in ammatory and neuropathic pain (Falk and Dickenson 2014), and often comes with concurrent depression, cognitive impairment, and other diseases (Feller et al 2019;Liu et al 2021). It has been reported that the differences between the sexes were minor and did not affect the overall progression of the pain state (Falk et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…We recently delineated a new physiological role for PRG-1 in chronic pain where we found that hippocampal PRG-1 relieves pain and depressive-like behaviors caused by bone cancer pain via P2X 7 R/PRG-1/PP2A pathway regulation of dendritic spine density in a cell-autonomous fashion (Liu et al, 2021a). We also found that hippocampal PRG-1 expression was upregulated as a compensatory protective effect in response to the bone cancer-induced pain (Liu et al, 2021a).…”
Section: Ll Open Accessmentioning
confidence: 94%
“…To date, studies on PRGs family have mainly focused on neuropsychiatric diseases and nerve injuries such as epilepsy (Ni et al, 2009;Trimbuch et al, 2009;Vogt et al, 2017), schizophrenia (Thalman et al, 2018;Vogt et al, 2016), memory disorders (Liu et al, 2016), nerve trauma (Hashimoto et al, 2013;Peeva et al, 2006), and sensory discrimination deficit (Cheng et al, 2016;Unichenko et al, 2016). We recently delineated a new physiological role for PRG-1 in chronic pain where we found that hippocampal PRG-1 relieves pain and depressive-like behaviors caused by bone cancer pain via P2X 7 R/PRG-1/PP2A pathway regulation of dendritic spine density in a cell-autonomous fashion (Liu et al, 2021a). We also found that hippocampal PRG-1 expression was upregulated as a compensatory protective effect in response to the bone cancer-induced pain (Liu et al, 2021a).…”
Section: Ll Open Accessmentioning
confidence: 99%